Improving reading comprehension of explanatory texts in indonesian language subject, fifth grade students through RADEC learning model - Nopiyanti, Nopiyanti; Altaftazani, Deden Herdiana; Kuswendi, Uus (Sekolah Pascasarjana UPI, 2024)
This study aims to improve the reading comprehension of explanatory texts in Indonesian subjects, fifth grade elementary school students through a problem based learning model based on RADEC. The subjects of this study were the fifth grade students of SD Gemala Ananda as many as 16 people. The method of data collection was done through test techniques in the form of multiple choice test questions and non-tests in the form of observation sheets and interviews. This classroom action research was conducted in two cycles, each cycle having systematic steps consisting of action planning, implementation, and observation and reflection. The results of this study indicate that the use of the RADEC-based problem-based learning model can improve the reading comprehension of the fifth grade elementary school explanatory text. In addition, student activities in learning are increasing and more interactive. Students are also more critical and dare to express their ideas, and can find answers to the problems presented by the teacher.